PENGARUH MARKETING STORYTELLING TIKTOK TERHADAP MINAT BELI KONSUMEN DI KEIKAKERY KOTA BATAM - Myra Humayrah; Dailami; Moh. Thamdzir; Wahyudi Ilham; Haufi Sukmamedian (Puslitabmas Batam Tourism Polytecnic, 2026)
This study aims to analyze the influence of marketing storytelling through the TikTok platform on consumer buying interest in Keikakery, Batam City. The phenomenon of using TikTok as a creative promotional medium has encouraged many culinary business actors to utilize story-based content to build emotional closeness with consumers. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to followers of the Keikakery TikTok account and consumers who are exposed to storytelling content. Data analysis was carried out using simple linear regression to see the magnitude of the influence of storytelling variables on buying interest. The results of the study show that TikTok storytelling marketing has a positive and significant effect on consumer buying interest. Narrative elements such as storyline, authenticity, relevance, product visualization, and emotional messages have been proven to increase consumer interest, trust, and desire to buy Keikakery products. The more interesting and relevant the storytelling content presented, the higher the buying interest formed. This research emphasizes that TikTok is an effective marketing medium in strengthening brand identity and influencing consumer behavior, so that storytelling strategies can be used as the main approach in developing Keikakery's digital promotion strategy in the future.